THE EXISTENCE OF WIHARA II DHARMA AMURVA BHUMI (KRAMAT AYAM SENEN) AFTER REORGANIZATION OF THE SEGITIGA SENEN AND ITS SURROUNDINGS IN 1967 - Majaputera Karniawan; Arya Whisnu Karniawan (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
The existence of Pasar Senen cannot be separated from Kramat Ayam which known build in early 20th century until 1921 on Jl. Kali Lio, because a stone with Chinese script was found loose from a Chinese grave and was considered sacred (Kramat), then moved to Jl. Pasar Senen Dalam III (formerly Gg. Tjap Pek Keng 十八間) became Wihara I in 1921 until it was closed on November 18, 1968 due to the impact of the reorganization of Segitiga Senen area and its surroundings known as the ‘Proyek Senen’ project in the era of Governor Ali Sadikin, since then its existence has not been heard again in literature sources. Apparently through field research it is known that this temple still exists under the name 'Wihara II Dharma Amurva Bhumi (Kramat Ayam Senen)' Jl. Kramat Jaya Baru Blok G3 No.362a, Johar Baru, Kramat, Central Jakarta, so that the research questions arise: (1) Why did the temple move to its current location? (2) How is the existence of religious activities in this temple since moving to a new location until now? And (3) What are challenges faced by the temple in maintaining its existence, now and future? This study uses a Qualitative Case Study approach with library data collection, activity observations, and informant interviews. The data analysis technique uses Milles, Hubberman, and Saldana (2014). Results of the study provide new explanations about (1) Kaleidoscope of the existence of Kramat Ayam from its inception until now, (2) Sacred figures (3) Prayer activities and congregational services at this temple, and (4) Challenges to the existence of the temple in regeneration of congregation and sustainability of management.